Numerical investigation of the multi-physics coupling effect of supersonic projectile on the cross section of terminal ballistics - L. Shen; D. Chen; H. Sun; Z. Yang (AIP Advances)
This study numerically investigates the multi-physics coupling effects of supersonic projectiles on terminal ballistics, focusing on shock wave interactions and their impact on measurement accuracy. A novel acoustic-optic coupling detection method is introduced, capable of capturing refractive index changes induced by shock waves. Using COMSOL simulations, the research demonstrates that this method offers superior sensitivity compared to traditional approaches, providing a precise way to determine projectile incidence angles. The findings have significant implications for improving measurement accuracy in hypersonic weapon systems.